2005
DOI: 10.1152/ajpheart.00088.2004
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of epicardial coronary capillary hemodynamics during reactive hyperemia and during adenosine administration by intravital video microscopy

Abstract: Using high-resolution intravital charge-coupled device video microscopy, we visualized the epicardial capillary network of the beating canine heart in vivo to elucidate its functional role under control conditions, during reactive hyperemia (RH), and during intracoronary adenosine administration. The pencil-lens video-microscope probe was placed over capillaries fed by the left anterior descending artery in atrioventricular-blocked hearts of open-chest, anesthetized dogs paced at 60-90 beats/min (n = 17). In i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 39 publications
5
42
0
Order By: Relevance
“…The lens-tip pressure was kept to a minimum (Ͻ2 mmHg), and the RV and LV pressures did not change. In dogs, we also confirmed that the pressure due to the lens probe was close to zero near the end of diastole (16). Thus we were confident that we could visualize coronary microvessels in situ in the rat RV with minimal interference from the microscopy system.…”
Section: Discussionsupporting
confidence: 74%
“…The lens-tip pressure was kept to a minimum (Ͻ2 mmHg), and the RV and LV pressures did not change. In dogs, we also confirmed that the pressure due to the lens probe was close to zero near the end of diastole (16). Thus we were confident that we could visualize coronary microvessels in situ in the rat RV with minimal interference from the microscopy system.…”
Section: Discussionsupporting
confidence: 74%
“…Several previous studies in dogs have compared peak coronary hyperemia after occlusion vs. hyperemia induced by intravenous or intracoronary administration of pharmacological agents. These studies have reported similar results between the two interventions (4,19), as well as higher values during RH (9) or higher values with vasodilators (1,11,33). Differences in agents, concentrations, and route of administration seem to underlie the reported disparity.…”
Section: Rh Vs Ahmentioning
confidence: 63%
“…The selective increase in porosity of the glycocalyx might be indicative of an increased plasma flow through this layer, thereby explaining the increase in capillary tube hematocrit during adenosine (12). This increase in functionally perfused capillary volume might underlie the mismatch that has been reported between increases in estimated epicardial capillary volumetric flow and coronary arterial flow during AH but not RH (11).…”
Section: Rh Vs Ahmentioning
confidence: 96%
“…After clamping of arterial perfusion line, systolic coronary venous outflow still persists for several heart beats [9,29,47], due to residual blood pooled in the intramyocardial capacitance vessels. To visualize transmural microvascular diameter and flow changes during a cardiac cycle, we developed three types of portable needle-probe videomicroscope with a chargedcoupled device (CCD) camera depending on measuring objectives [19,27,33,53,57]. Type 1 (prototype) The objective of the prototype is to visualize the phasic diameter changes of transmural arterioles and venules.…”
Section: Introductionmentioning
confidence: 99%